Correction:

`y'=-ln(3)*1/(ln(x))^2 *1/x = -(ln(3))/(x(lnx)^2)`

Or

`y'=-(log_x(3))/(xlnx)`

First, simplify the given function using the change of base formula for logarithms:

`log_b (a) = (log_c (a))/(log_c (a))`

Applying this formula to the given function in order to change to logarithm with base e (natural log) , we get

`y = log_x(3) = (ln(3))/(ln(x))`

The derivaltive can now be found using the chain rule and the fact that `(ln(x))' = 1/x` :

`y' = ln(3) * 1/(ln(x))^2 * 1/x = (ln(3))/(x(ln(x))^2)`

We could also rewrite it back as a log with base x:

`y' = (log_x(3))/(xlnx)`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now